Corporate social responsibility and an enterprise’s operational efficiency: considering competitor’s strategies and the perspectives of long-term engagement - Yang, Shou-Lin (Quality & quantity, 2016)
This study employs an existing slacks-based measure-data envelopment analysis to calculate an enterprise’s operational efficiency. With Tobit and threshold regressions, the author analyses the effects of the corporate social responsibility (CSR) engagement of both a focal company and its competitors on its operational efficiency. Long-term CSR engagement plays an important role in corporate efficiency. A firm may enhance the effects of its short-term CSR engagement and decrease those of its competitor’s long-term CSR engagement on efficiency by increasing its own long-term CSR engagement. When a competitor’s long-term CSR engagement is high, its short-term CSR engagement will decrease corporate efficiency. However, when the competitor’s long-term CSR engagement is low, the firm’s long-term CSR engagement will improve its efficiency.